Characteristics of evapotranspiration and crop coefficient correction at a permafrost swamp meadow in Dongkemadi watershed, the Source of Yangtze River in interior Qinghai-Tibet Plateau - Guo, Hao-nan; He, Xiaobo; ding, yongjian; Fan, Yawei; Fu, Hui; Hong, Xiaofeng (Authorea, Inc., 2022)
Evapotranspiration is an essential element of the hydrological process. Estimating evapotranspiration at polar regions is challenging. Different results were obtained based on observation and simulation by the FAO Penman-Monteith equation (FAO P-M), and FAO P-M was found to be inadequate to estimate the evapotranspiration in alpine swamp meadows with exposed water. Based on the characteristics and main influencing factors of observed actual evapotranspiration, the coefficient of FAO P-M was modified to better simulate the actual evapotranspiration in the alpine swamp meadow area. Our results indicated that (1) both ET measured by the eddy covariance system and ET calculated by FAO P-M had the same trend at the daily and annual scales and hysteresis was confirmed. (2) The annual ET was 566.97 mm and annual ET /P was 0.76, and about 11.19% of ET occurred during night. (3) The main influencing factors during growing season were the R , vapor pressure deficit (VPD), and g , and those during non-growing season were volumetric soil water content (VSWC), R , soil temperature (ST), precipitation (P), and W . (4) The basic corrected K was 1.14 during the initial and mid-growing season, 1.05 during subsequent growing season, and 0-0.25 during the non-growing season.